2016
DOI: 10.1042/cs20150103
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase 2 plays a role in experimental corneal neovascularization

Abstract: Corneal neovascularization, the growth of new blood vessels in the cornea, is a leading cause of vision impairment after corneal injury. Neovascularization typically occurs in response to corneal injury such as that caused by infection, physical trauma, chemical burns or in the setting of corneal transplant rejection. The NADPH oxidase enzyme complex is involved in cell signalling for wound-healing angiogenesis, but its role in corneal neovascularization has not been studied. We have now analysed the role of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…We confirmed that NOX2 is also necessary for the proangiogenic effect of dRP in vivo . This is in line with two recent studies showing a role for this member of the NOX family in the stimulation of angiogenesis in vivo , although it should be emphasized that these reports, in contrast to the present study, did not provide clarity on the underlying molecular mechanisms ( 10 , 70 ).…”
Section: Discussionsupporting
confidence: 87%
“…We confirmed that NOX2 is also necessary for the proangiogenic effect of dRP in vivo . This is in line with two recent studies showing a role for this member of the NOX family in the stimulation of angiogenesis in vivo , although it should be emphasized that these reports, in contrast to the present study, did not provide clarity on the underlying molecular mechanisms ( 10 , 70 ).…”
Section: Discussionsupporting
confidence: 87%
“…It is worth noting that the nitrate injury is associated with an induction of the proangiogenic VEGF-A but not profibrotic factor TGFβ1. 13 In contrast, NaOH injury stimulates the expression of both VEGF and TGFβ1 in the burnt corneas, consistent with recent findings by Gu et al 28 In this regard, both Nox2 and Nox4 appear to regulate the initial inflammation and neovascular responses in the corneas up to day 7 following chemical insults. The induction of TGFβ1 is ablated in burnt corneas from Nox4 KO mice, which actually show a lower degree of opacity and collagen accumulation in the burnt corneas when compared to the WT.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, the details of these mechanisms of response to injury vary a little between different models of corneal injury. Chan et al 13 used acidic silver nitrate to inflict an injury to the corneal surface, and this results in an upregulation of Nox2 mRNA and a downregulation of the Nox4 gene over 7 days. In that study, Nox2 upregulation was found to be associated with inflammation and neovascularization in the burnt corneas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, topical administration of 0.5% Alcaine for local anesthesia was performed, followed by pressing the tip of an applicator containing silver nitrate/potassium (Grafco) to the center of the cornea steadily for 8 seconds. 22 The excess of nitrate was eliminated by washing with 5 mL of saline solution. A burned cornea causing opacity on the eye was observed.…”
Section: Huvec-migration Assaymentioning
confidence: 99%